Microsimulation analysis of the impact of indirect tax benefits on income distribution and poverty alleviation in Tanzania: An application of TAZMOD - Asiya Maskaeva; Zanda Bochkaeva; Joel Mmasa; Mgeni Msafiri; Eric Iramba (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper analyses the impacts of indirect tax policy reforms on income distribution and poverty in Tanzania by applying a standard static microsimulation model TAZMOD v1.8. The simulations model two indirect tax reforms involving changes to the excise duty and value-added tax rates on alcoholic beverages and tobacco products, and changes to employers' and employees' contributions to the National Health Insurance Fund. The results of the first reform find a positive effect on government tax revenue and a neutral effect on income distribution and poverty. The results of the second reform find a positive effect on household income distribution and consumption. The findings show that, despite increasing unequal income distribution, poverty indicators fell.
Keywords: D31; H25; I38; 330; income distribution; poverty; tax-benefit reforms; microsimulation